Analisis Data Mining Algoritma Decision Tree Pada Prediksi Persediaan Obat (Studi Kasus : Apotek Franch Farma) - Dwita Elisa Sinaga; Agus Perdana Windarto; Rizki Alfadillah Nasution (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Medicine is an object that is formulated by medical personnel to assist in preventing, healing, recovering, and improving the health of patients. Pharmacies are places that provide various types of drugs that are needed by patients, but pharmacies often have problems in providing drugs which result in a shortage of goods when someone needs it. aspect. This problem will be solved by using the C4.5 algorithm based on data obtained from the Franch Farma Pharmacy. The purpose of this study is to predict the supply of drugs that will be needed by dividing them into 6 variables, namely the name of the item, type of drug, inventory, initial stock, ending stock, and goal. The research test process uses Rapidminer software to create a decision tree. And the results obtained are 12 rules to predict drug supplies to be carried out by Franch Farma Pharmacy with an accuracy rate of 80.00%. From the results of the analysis, it is hoped that it can help pharmacists in making drug supplies more effective and efficient.